Whole-genome identification and functional analysis of grape bHLH transcription factors: new insights into the regulation of monoterpene biosynthesis - Sun, Qian; Liu, Zhenhua; Wang, Xiaoyue; Yan, Ailing; Ren, Jiancheng; Wang, Huiling; Sun, Lei (Frontiers in Plant Science, 2025)
Basic/helix-loop-helix (bHLH) transcription factors play critical roles in the regulation of plant secondary metabolism, but the molecular mechanisms involved in monoterpene synthesis by the grape bHLH family have not been systematically resolved. In this research, 12 VvbHLHs were detected in the grape genome, encoding 468–696 amino acids with molecular masses ranging from 52.5 to 77.5 kDa. Phylogenetic analyses showed that grapevine bHLH family members are closely related to dicotyledonous plants such as Pyrus bretschneideri and Malus domestica. These VvbHLHs were mainly localized in the nucleus, and their promoter regions were enriched for cis-acting elements linked to developmental stages and stress resistance. Spatio-temporal expression profiling indicated that VvbHLHs were significantly upregulated during fruit ripening, with the expression of VvbHLH9 (VvbHLH041) significantly and positively correlated with monoterpene accumulation. Subcellular localization analysis showed that VvbHLH9 was localized in the nucleus; and transient overexpression assays revealed that VvbHLH9 significantly activated monoterpene skeleton genes (VvDXS1 and VvDXS4) and synthase genes (VvTPS31, VvTPS32, and VvTPS35) to promote the accumulation of monoterpene metabolites, such as terpinolene, allo-ocimene, nerol, geraniol, cis-furan linalool oxide and linalool. Notably, VvbHLH9 lacked the typical bHLH-MYC_N structural domain, suggesting that it may affect the monoterpene metabolic network through a non-classical regulatory mechanism. The present study uncovers the modulatory function of grapevine bHLHs on the synthesis of monoterpene metabolites, providing new targets for grapevine fruit quality improvement and molecular breeding.